2021
DOI: 10.1071/mf20204
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific variation in diel patterns of rocky reef use suggests temporal partitioning in Port Jackson sharks

Abstract: Limited information exists about the temporal residency patterns of marine predators, especially at the individual level. Temporal partitioning of resources can reduce intra-specific competition, but this has seldom been examined in predators in marine ecosystems. Here, we used 8 years of acoustic telemetry data from 27 receivers deployed in a large coastal embayment to examine the temporal residency of 51 Port Jackson sharks (Heterodontus portusjacksoni), during their breeding season. We found that the reside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 66 publications
1
5
0
Order By: Relevance
“…The oxygen uptake rate ( Ṁ O 2 ) patterns of epaulette sharks over a 24-h period are remarkably similar to distinct diel ventilation and activity patterns reported for other benthic sharks, including swell ( Cephaloscyllium ventriosum ), draughtboard ( Cephaloscyllium isabellum ), Port Jackson ( Heterodontus portusjacksoni ), and horn ( Heterodontus francisci ) sharks (Nelson and Johnson, 1970; Bass et al, 2021; Kadar et al, 2019; Kelly et al, 2020, 2021). Given the significantly lower metabolic rate estimates during the day, our findings also strongly support the behavioral sleep hypothesis proposed by Kelly et al (2019, 2020, 2021).…”
Section: Discussionsupporting
confidence: 66%
“…The oxygen uptake rate ( Ṁ O 2 ) patterns of epaulette sharks over a 24-h period are remarkably similar to distinct diel ventilation and activity patterns reported for other benthic sharks, including swell ( Cephaloscyllium ventriosum ), draughtboard ( Cephaloscyllium isabellum ), Port Jackson ( Heterodontus portusjacksoni ), and horn ( Heterodontus francisci ) sharks (Nelson and Johnson, 1970; Bass et al, 2021; Kadar et al, 2019; Kelly et al, 2020, 2021). Given the significantly lower metabolic rate estimates during the day, our findings also strongly support the behavioral sleep hypothesis proposed by Kelly et al (2019, 2020, 2021).…”
Section: Discussionsupporting
confidence: 66%
“…Nonetheless, Bass et al . (2021) and the results of this study suggest that there may be some diel variation in the residency of H. portusjacksoni during the breeding season and further investigation is warranted.…”
Section: Discussionmentioning
confidence: 70%
“…These findings also support those of Bass et al . (2021) who found that individual H. portusjacksoni exhibited variation in their temporal residency patterns and periodicity of site use within Jervis Bay. In addition, two females were detected by receivers in Jervis Bay outside of the breeding season, suggesting that H. portusjacksoni may exhibit partial migration with some individuals remaining in or near the bay throughout the year.…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing body of evidence that elasmobranchs of the same sex and age class exhibit intraspecific variation in residency, movement and habitat use within a season or on an annual cycle (Vaudo et al 2014;Bass et al 2021a;Espinoza et al 2021). Intraspecific variation in migration behaviour in other taxa, in particular overwintering or nonbreeding locations of birds (Saino et al 2004;Leyrer et al 2013;Goodenough et al 2017;Steenweg et al 2017), can influence the fitness and reproductive success of individuals, with consequences for their survival and resilience.…”
Section: Discussionmentioning
confidence: 99%
“…Additional receivers were deployed around the Australian coastline (n = 112 between Jervis Bay and Tasmania), as a part of the Integrated Marine Observing System (IMOS) animal-tracking database, a national collaborative research initiative of various universities, government and private research institutions. Details on residency, local movements and migration patterns of Port Jackson sharks based on these data have previously been described by Bass et al 2017Bass et al , 2021aBass et al , 2021b. The migration data from Bass et al (2017) are used here to validate the application of isotopes to understand population-level movement behaviour.…”
Section: Capture and Tagging Proceduresmentioning
confidence: 99%